2014
DOI: 10.1007/s00401-014-1336-5
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation-prone c9FTD/ALS poly(GA) RAN-translated proteins cause neurotoxicity by inducing ER stress

Abstract: The occurrence of repeat-associated non-ATG (RAN) translation, an atypical form of translation of expanded repeats that results in the synthesis of homopolymeric expansion proteins, is becoming more widely appreciated among microsatellite expansion disorders. Such disorders include amyotrophic lateral sclerosis and frontotemporal dementia caused by a hexanucleotide repeat expansion in the C9ORF72 gene (c9FTD/ALS). We and others have recently shown that this bidirectionally transcribed repeat is RAN translated,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
346
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 305 publications
(370 citation statements)
references
References 78 publications
(136 reference statements)
23
346
1
Order By: Relevance
“…Expanded repeats also undergo abnormal repeat associated non-ATG (RAN) translation (Zu et al, 2011). In patients, these proteins form stellate cytoplasmic inclusions in degenerate and non-degenerate brain regions Mackenzie et al, 2013;Mann et al, 2013;Mori et al, 2013b;Zu et al, 2013) and some have been shown to disrupt cellular function and cause toxicity when overexpressed in model systems (Kwon et al, 2014;Mizielinska et al, 2014;Wen et al, 2014;Zhang et al, 2014). Due to the number and complexity of these potential mechanisms, it remains unclear which among them contributes most to disease pathogenesis in patients.…”
Section: Introductionmentioning
confidence: 99%
“…Expanded repeats also undergo abnormal repeat associated non-ATG (RAN) translation (Zu et al, 2011). In patients, these proteins form stellate cytoplasmic inclusions in degenerate and non-degenerate brain regions Mackenzie et al, 2013;Mann et al, 2013;Mori et al, 2013b;Zu et al, 2013) and some have been shown to disrupt cellular function and cause toxicity when overexpressed in model systems (Kwon et al, 2014;Mizielinska et al, 2014;Wen et al, 2014;Zhang et al, 2014). Due to the number and complexity of these potential mechanisms, it remains unclear which among them contributes most to disease pathogenesis in patients.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, gene expression analysis of ALS brain tissue from patients carrying C9orf72 mutations, the most relevant genetic alteration in ALS, mutations shows major alteration in ER stress-related genes in cerebellum [116]. In agreement with this, expression of RAN peptides derived from C9orf72 mutation in cell culture also triggers abnormal levels of ER stress [117].…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 80%
“…Indeed, biochemical data suggested that as many as 50% of the proteasome complexes in the neuron become highly entangled within poly(GA) ribbons. Removal of proteasomes from their normal location in cells through this sequestration mechanism might explain the reduced proteasomal activity in cells harbouring these aggregates 4,8 . Complexes called ribosomes, which mediate protein production and are comparable in size to proteasomes, were largely excluded from poly(GA) ribbons, suggesting that poly(GA) aggregates are actively recruited or retained by proteasomes.…”
Section: Years Agomentioning
confidence: 99%